Hubungan Paritas dengan Kejadian Berat Bayi Lahir Rendah di Klinik Fatiha - Yuswitira, Melly; Syahda, Syukrianti; Harahap, Dewi Anggriani (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
According to WHO, the world infant mortality rate (IMR) is still quite high, namely 54 per 1000 live births. Causes of death include LBW (38.94%), neonatal asphyxia (27.97%), infections including neonatal sepsis (5.68%), pneumonia 5.68%) and congenital abnormalities. Low birth weight is a condition when a baby is born with a body weight of less than 2500 grams. The aim of this research is to determine the relationship between parity and the incidence of low birth weight babies at the Fatiha Clinic in 2022. This research design uses quantitative research methods with a case control approach. Case samples were taken using total sampling technique and control samples using simple random sampling. The research was carried out at the Fatiha Clinic. The research population of all newborns at the Fatiha Clinic was 174 newborns. There were 35 newborns who experienced Low Birth Weight and 139 babies who did not experience Low Birth Weight. The research uses a secondary data checklist sheet. Univariate and Bivariate data analysis using the Chi-Squere test. These results show that there is a relationship between parity and the incidence of low birth weight babies, with a p value of 0.000 <0.05. For this reason, the clinic frequently provides health education to the public regarding the importance of paying attention to parity factors in planning pregnancy.